PERBEDAAN LEBAR CELAH TEPI TUMPATAN SEMEN IONOMER KACA MODIFIKASI RESIN NANO DAN MODIFIKASI RESIN - Yuliana Ratna Kumala; Dini Rachmawati; Amanda Andika Sari (Odonto : Dental Journal, 2017)
Background: One over many ways to treat dental caries is by restoration.Glass ionomer cement (GIC) is the restorations material that bonds physically and chemically to tooth structure. GIC has been developed by combining the conventional material with monomer resin, known as resin  modified GIC (RMGIC). Presently, with the development of nano  technology, RMGIC restoration also available in the form of nano   particles, called nanofilled RMGIC (RMGICn). One disadvantage of GIC is the marginal gap which may affects the durability ofrestoration. Purpose: The purpose of this study to compare the marginal gap width of RMGIC and nanofilled RMGIC.Methods: This study used scanning electron microscope (SEM) to observing and measuring the marginal gap width in two kelompoks of 9 maxillary first premolar teeth. The first kelompok restored with RMGIC, the second kelompok restored with nanofilled RMGIC. Following immersion in artificial saliva and the teeth were thermocycled at a temperature of 5oC, 37oC, and 55oC (250 cycles) 1 minute each. Data analysis was done using independent t-test with 95% confidence interval (α = 0.05).Results: Statistical test showed a significant difference for marginal gap width in both kelompok (p = 0.000).Conclusion: There is marginal gap in RMGIC and RMGICn restoration. RMGIC restoration presented lower marginal gap width than RMGIC.